2013
DOI: 10.1016/j.surfcoat.2013.06.101
|View full text |Cite
|
Sign up to set email alerts
|

Influence of substrate material on the life of atmospheric plasma sprayed thermal barrier coatings

Abstract: Thermal barrier coatings (TBCs) are used in gas turbines to prolong the life of the underlying substrates and to increase the efficiency of the turbines by enabling higher combustion temperatures. TBCs may fail during service due to thermal fatigue or through the formation of non-protective thermally grown oxides (TGOs). This study compares two atmospheric plasma sprayed (APS) TBC systems comprising of two identical TBCs deposited on two different substrates (Haynes 230 and Hastelloy X). The thermal fatigue li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…Therefore, the internal oxidation 1 of the rough bond coat layer is inevitable during long-term exposure at high temperature. Actually, the internal oxidation is a common phenomenon even for a single layered bond coat [10,[14][15][16]. For example, it was reported that, for an APS bond coat, the amount of the internal oxides can be up to 50% (in volume) after 120 cycles at 1121 °C [15].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Therefore, the internal oxidation 1 of the rough bond coat layer is inevitable during long-term exposure at high temperature. Actually, the internal oxidation is a common phenomenon even for a single layered bond coat [10,[14][15][16]. For example, it was reported that, for an APS bond coat, the amount of the internal oxides can be up to 50% (in volume) after 120 cycles at 1121 °C [15].…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…The thicker TGO layer results in a markedly large stress intensity factor during the intermediate and late stage of crack growth, although it is slightly lower during the initiation of crack. As a result, the fast growth rate of the TGO layer leads to the short lifetime performance of the TBC [45]. The TBC is a multilayer coating system including superalloy, intermetallic bond coat, TGO layer, and 13 ceramic top coat.…”
Section: Furnace Cyclic Thermal Fatigue Testmentioning
confidence: 99%
“…Faster Al depletion may promote the formation of spinels in the coating and eventually reduce the overall thermal fatigue life of the TBC system. Eriksson et.al have found a significant difference in the TCF life time for the same TBC coatings but on two different substrates [40]. Apart from the Al inter-diffusion, diffusion of other elements between the coating and the substrate is also undesirable as the elements that give the properties and functionality for coating/substrate tend to diffuse out.…”
Section: Fig 8 Schematic Illustration Of a Thermal Cycling Test Rigmentioning
confidence: 99%